Obesity determinants among Malaysian schoolchildren: What is new? - Aryati, Ahmad; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Engku Fadzli Hasan, Syed Abdullah; Mohd Razif, Shahril; Zulaily, N.; Abdul Manan, N.S; Amin, R.M; Ahmed, A (2017)
Obesity among schoolchildren has been regarded as one of the most serious public health challenges in this decade. This problem has now become more evident in the developing countries including Malaysia. It is linked with numerous risk factors mainly unhealthy lifestyle(1) . Despite many surveys that have been conducted globally, the latest data on its determinants among Malaysian schoolchildren, particularly in sub-urban state like Terengganu, is limited. Therefore, this study aimed to provide the current analysis on obesity determinants including demographic, socioeconomic status, dietary intake, physical activity, and physical fitness level and its relationship with childhood obesity. Using a cross-sectional study design, a total of 1,404 schoolchildren were involved in the study (46·3 % boys and 53·7 % girls; 67·7 % urban and 32·3 % rural). Data on demographic and socioeconomic were gathered using a selfadministered questionnaire. Height and body weight were measured and BMI-for-age Z-score was calculated using WHO AnthroPlus software and compared with WHO BMI-for-age Z-score classifications (2007)(2) . Dietary intake and physical activity level were measured using FFQ and c-PAQ, respectively, whereas physical fitness level was assessed using SEGAK test, a standardised fitness norm test for Malaysian students. All data were analysed using multivariable analysis